2019
DOI: 10.1242/dev.176586
|View full text |Cite
|
Sign up to set email alerts
|

De novo genesis of retinal ganglion cells by targeted expression of Klf4 in vivo

Abstract: Retinal ganglion cell (RGC) degeneration is a hallmark of glaucoma, the most prevalent cause of irreversible blindness. Thus, therapeutic strategies are needed to protect and replace these projection neurons. One innovative approach is to promote de novo genesis of RGCs via manipulation of endogenous cell sources. Here, we demonstrate that the pluripotency regulator gene Krüppel-like factor 4 (Klf4) is sufficient to change the potency of lineage-restricted retinal progenitor cells to generate RGCs in vivo. Tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 83 publications
0
15
0
Order By: Relevance
“…This study showed that Klf4 induced the reactivation of the early neurogenic program in late progenitors, changing their competence to generate RGCs that properly localized to the inner retina and projected axons into the optic nerve head (Rocha-Martins et al, 2019). The precise mechanism underlying the effect of Klf4 in late progenitors is still unknown, but we hypothesize that Klf4 reactivates the molecular program for RGC differentiation through its properties as a pioneer factor, combined with the direct or indirect induction of Atoh7 (Chronis et al, 2017;Rocha-Martins et al, 2019). Although these results are promising, the detailed characterization of the transcriptional signature, subtype, and function of these induced RGCs, as well as their capacity to connect within the retina and with their brain targets remains to be defined.…”
Section: Molecular Program For Rgc Generation Temporal Patterning Of mentioning
confidence: 83%
See 3 more Smart Citations
“…This study showed that Klf4 induced the reactivation of the early neurogenic program in late progenitors, changing their competence to generate RGCs that properly localized to the inner retina and projected axons into the optic nerve head (Rocha-Martins et al, 2019). The precise mechanism underlying the effect of Klf4 in late progenitors is still unknown, but we hypothesize that Klf4 reactivates the molecular program for RGC differentiation through its properties as a pioneer factor, combined with the direct or indirect induction of Atoh7 (Chronis et al, 2017;Rocha-Martins et al, 2019). Although these results are promising, the detailed characterization of the transcriptional signature, subtype, and function of these induced RGCs, as well as their capacity to connect within the retina and with their brain targets remains to be defined.…”
Section: Molecular Program For Rgc Generation Temporal Patterning Of mentioning
confidence: 83%
“…This may be due to redundancy with other Klf family members (Jiang et al, 2008), since many are expressed in the developing retina (Moore et al, 2009;Njaine et al, 2014). We recently showed that overexpression of Klf4 in late retinal progenitors generates induced RGCs outside of their developmental window (Figure 1; Rocha-Martins et al, 2019). This study showed that Klf4 induced the reactivation of the early neurogenic program in late progenitors, changing their competence to generate RGCs that properly localized to the inner retina and projected axons into the optic nerve head (Rocha-Martins et al, 2019).…”
Section: Molecular Program For Rgc Generation Temporal Patterning Of mentioning
confidence: 85%
See 2 more Smart Citations
“…Measurements of visual acuity by optomotor response were performed using OptoMotry as previously described (Cavalheiro et al, 2017;Rocha-Martins et al, 2019). Visual accuracy threshold was determined by systematic increments of the spatial frequency until the animal no longer responded.…”
Section: Optomotor Response Testmentioning
confidence: 99%